The nature of early farming in Central and South-east Europe - Bogaard, Amy (Documenta Praehistorica, 2004)
This paper summarises models of crop and animal husbandry in Neolithic Europe and reviews the relevant evidence from three regions: the western loess belt and Alpine Foreland; the Great Hungarian Plain; and the southern Balkans and Greece. Intensive mixed farming (small-scale, labour-intensive cultivation integrated with small-scale herding) emerges as the most plausible model across these regions. Such continuity is in some ways counter-intuitive given climatic variability across Europe and archaeological diversity in settlement and house forms etc. It is argued that variability in the form of Neolithic settlements (nucleated versus dispersed, 'tell' versus 'flat' sites) should beunderstood not as a reflection of radically different farming practices but rather as different social permutations of the same basic farming and herding pattern.
Keywords: Central Europe; srednja Evropa; jugovzhodna Evropa; arheološke najdbe; neolitik; naselja; kmetijstvo; agriculture; poljedelstvo; animal husbandry; živinoreja